Rock Salt Properties for Gas Storage in Mined Caverns: Part I–Short-Term Deformation and Yield, Long-Term Creep, and Gas Sealing Capacity - J. Sarout; M. Sari; L. Esteban; P. P. Mandal; J. Bourdet; D. Nguyen; J. Strand; E. Frery; L. Imbert; A. Francois; L. Langhi; D. Mallants (Rock Mechanics and Rock Engineering, 2026)
Deep rock salt formations can be drilled and solution-mined into caverns for permanent waste disposal, or temporary energy storage (natural gas/compressed air/hydrogen) to alleviate the intermittency of wind/solar energy. We report here the results of the laboratory appraisal of the key properties of a thick Devonian rock salt formation in the Canning Basin (Western Australia). Two representative but contrasting lithofacies were identified: a clean lithofacies made of nearly pure halite, and a dirty lithofacies comprising anhydrite, and dolomite/quartz inclusions. On each lithofacies, we conducted a mineralogical, microstructural and petrophysical characterisation, and a long-term four-stage triaxial test to simulate the impact of depth and anthropogenic stress perturbations. Strains and ultrasonic P-/S-wave velocities were monitored, and at specific stages of the triaxial test, long-term gas transmissivity and creep tests were conducted for up to 16 and 42 days, respectively. At all the triaxial stresses explored, including the in-situ conditions, the oven-dry clean salt facies exhibits a typical gas permeability of 5.10 –5 mD = 5.10 –20 m 2 , whereas the dirty salt is 100 to 1000 times more permeable to gas. The estimated steady-state creep rates are consistent with the extensive collection of literature data also reported here. The dominant creep mechanism is likely dislocation glide, complemented by frictional sliding where damage might exist. Pressure-solution creep is probably not dominant here, especially within the testing time scale. However, water is likely present in deep salt bodies and around man-made salt caverns, promoting overall creep through pressure-solution, and damage healing, hence reducing gas permeability even further.

SARAL/AltiKa Wet Tropospheric Correction: In-Flight Calibration, Retrieval Strategies and Performances - B. Picard; M.-L. Frery; E. Obligis; L. Eymard; N. Steunou; N. Picot (Marine Geodesy, 2015)